2016
DOI: 10.3989/gya.1237153
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging and α-glucosidase inhibition, two potential mechanisms involved in the anti-diabetic activity of oleanolic acid

Abstract: SUMMARY:This work investigates the role of oleanolic acid (OA), isolated from the olive (Olea europaea L.) leaf, as a radical scavenger and inhibitor of the hydrolyzing enzymes of dietary carbohydrates. New evidence is provided showing that OA may capture 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) and peroxyl radicals, and also exert a strong and non-competitive inhibition of α-glucosidase (IC 50 10.11 ± 0.30 µM). The kinetic and spectrometric analyses performed indicate that OA interacts with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recommendations regarding overall diet composition, increased physical activity, weight loss, moderate consumption of alcohol and avoiding tobacco were given identically to both groups. This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA …”
Section: Discussionsupporting
confidence: 81%
“…This strong protective action against diabetes in humans is consistent with experimental evidence in animals showing improvements in glucose homeostasis, lipid metabolism and insulin signalling, as well as the reinforcement of the adaptive cell response to oxidative stress and inflammation, all recognized as pharmacological mechanisms of OA. [12][13][14][32][33][34] The PREDIABOLE study also suggests that the long-term administration of a daily dose of 30 mg OA is safe for prediabetic individuals as no adverse effects related to the intervention were either reported during the follow-up or during the two subsequent years. OA has been considered as a very safe over-the-counter drug used for hepatoprotection and for treating hepatitis in China for decades.…”
Section: Safety Of the Dietary Interventionmentioning
confidence: 91%
“…The results obtained in the different tests for pure OA agreed with those reported by Castellano et al . These authors found that OA showed no activity in inhibiting the DPPH radical, a low activity in scavenging the ABTS radical, and very low activity in protecting fluorescein in the ORAC assay.…”
Section: Resultssupporting
confidence: 90%
“…The results obtained in the different tests for pure OA agreed with those reported by Castellano et al 17 These authors found that OA showed no activity in inhibiting the DPPH radical, a low activity in scavenging the ABTS radical, and very low activity in protecting fluorescein in the ORAC assay. In contrast, Allouche et al 14 did observe radical scavenging activities for both OA and MA in the DPPH and ABTS tests, but these were very weak and dependent on the TA concentrations.…”
Section: Evaluation Of the Potential Antioxidant Activity Of Ta Concesupporting
confidence: 90%
See 1 more Smart Citation